Labor Market Participation of Married Women in Bangladesh - Khandker, Shahidur R. (The Review of Economics and Statistics, 1987)
ABS'DtAC'l'For a country such as Bangladesh, a nested multinomial logit model is utilized to test whether female time allocation is inflexibly fixed by local customs and whether informal activity is an independent category in a woman's choice structure of work.The econometric analysis of cross-sectional women's time-use data from rural Bangladesh suggests that a woman's activity as an unpaid labor in a family enterprise is not a distinct category in her choice structure of work.The results support the alternative hypothesis, however, that women's time-use patterns are not exclusively fixed by the society, but are partially influenced by individual-, household-, and community-level economic constraints.